Questionnaire-based assessment on knowledge, attitude and practice of fixed-dose combination in medical undergraduates of a tertiary care teaching hospital, Kanpur - Kushwaha, Virendra; Agrawal, Pooja; Sahu, Alpana; Pushkar, Pushpendra; Khan, Nasreen F.; Vekaria, Harsh (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Aim was to assess knowledge, attitude and practice of second-year medical undergraduates towards FDC. Methods: A cross-sectional questionnaire-based study was conducted among second-year medical undergraduates of GSVM, medical college, Kanpur in the form of a pre-test, and after sensitizing the students about FDC, the same questionnaire was given as a post-test. Results: A total of 251 students, 157 students participated in the pre-test and 140 participated in the post-test. The percentage of male students in pre and post-test were more (58% and 61.4%) compared to female students (42% and 38.6%). After conducting a post-test survey, there is a significant improvement in knowledge and attitude toward FDC. Conclusions: The inclusion of FDC in the undergraduate curriculum is a good initiative by NMC but there is a need to conduct more CME, symposiums, and workshops in medical colleges to update the knowledge regarding FDC among medical undergraduates.